2016
DOI: 10.1007/s10695-015-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increasing dietary levels of amino acid-supplemented soy protein concentrate and constant dietary supplementation of phosphorus on growth, composition and immune responses of juvenile Atlantic salmon (Salmo salar L.)

Abstract: Diets with 50 (SPC50), 65 (SPC65) and 80% (SPC80) substitution of prime fish meal (FM) with soy protein concentrate (SPC) were evaluated against a commercial type control feed with 35% FM replacement with SPC. Increases in dietary SPC were combined with appropriate increases in methionine, lysine and threonine supplementation, whereas added phosphorus was constant among treatments. Diets were administered to quadruplicate groups of 29 g juvenile Atlantic salmon were exposed to constant light, for 97days. On Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 69 publications
3
10
2
Order By: Relevance
“…No effects of the SPC inclusion levels on specific antibody production were detected, which is in line with the data from the study by Metochis et al [22], on increasing dietary SPC levels on larger size Atlantic salmon parr. Kiron et al [59][60] reported no changes in the specific antibody levels of rainbow trout fed on different dietary protein levels, suggesting that specific antibody production does not seem to depend on dietary protein quantity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…No effects of the SPC inclusion levels on specific antibody production were detected, which is in line with the data from the study by Metochis et al [22], on increasing dietary SPC levels on larger size Atlantic salmon parr. Kiron et al [59][60] reported no changes in the specific antibody levels of rainbow trout fed on different dietary protein levels, suggesting that specific antibody production does not seem to depend on dietary protein quantity.…”
Section: Discussionsupporting
confidence: 91%
“…Furunculosis is a highly infectious disease, causing serious fish losses, such as those observed during the epidemic of 1991-1992, which led to the loss of approximately 25% of the total Scottish salmon production [22]. Successful vaccination has enabled the disease to be brought under control and currently the majority of farmed Scottish and Norwegian Atlantic salmon are vaccinated against fununculosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While much effort has focused on evaluating the extent of SBM‐induced histological damage, SBM‐induced enteritis (SBMIE) (e.g., Bakke‐McKellep, Press, Baeverfjord, Krogdahl, & Landsverk, ; Bakke‐McKellep, Froystad et al., ; Bakke‐McKellep, Penn et al., ; Bakke‐McKellep, Koppang et al., ; Hedrera et al., ; Krogdahl, Bakke‐Mckellep, Roed, & Baeverfjord, ; Metochis et al., ; Rumsey, Siwicki, Anderson, & Bowser, ), the effects on the intestinal microbiota of fish were not reported until 2006. However, as the importance of the gut microbiota and our awareness of this complex microbial ecosystem have increased the interest in the factors that might modulate the intestinal microbial communities (Ringø et al., ).…”
Section: Effects Of Soybean Products On Gut Microbiotamentioning
confidence: 99%
“…() showed that saponins caused dose‐dependent increases in the severity of inflammation independent of the basal diet, with concomitant alterations in digestive functions and immunological marker expression. In the inflammatory states of SBMIE or SPCIE, plasma immunoglobulin level (Bakke‐McKellep et al., ; Metochis et al., ) and T‐cell numbers (Bakke‐McKellep, Froystad et al., ) were significantly increased. Although the physiology of the immune modulation is not completely understood at present, this activated immune responses may be related to an allergic reaction caused by SBM or SPC.…”
Section: Immunologymentioning
confidence: 99%